Modelo de mistura de regressão: uma abordagem bayesiana - Cotrim, Luiz Gabriel Fernandes (Universidade Federal de São Carlos, 2020)
In the current dissertation, we study the mixture regression models and present two Bayesian methodologies for their estimation. The first one considers the number of components is known and we propose the use of two Bayesian model selection criteria, DIC and EBIC, to identify the number of components. In the other one, we propose a reversible jump algorithm with splitmerge steps that estimates parameters and the number of components. We apply the proposed methodologies and also the EM algorithm, already available in R package, for simulated dataset and for Brazilian educational data, studying the relationship among the Basic Education Development Index and some socioeconomic and demographic data.
Regression mixture model: a bayesian approach
Keywords: Modelo de mistura; Modelo de mistura de regressão; Inferência Bayesiana; MCMC; EBIC; IDEB; Data-driven reversible jump; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::ANALISE DE DADOS; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::FUNDAMENTOS DA ESTATISTICA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA EM PROCESSOS ESTOCASTICOS; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA NAO-PARAMETRICA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::INFERENCIA PARAMETRICA; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::PLANEJAMENTO DE EXPERIMENTOS; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA::REGRESSAO E CORRELACAO